Pemanfaatan Teknik Rainwater Harvesting sebagai Pemenuhan Kebutuhan Air Domestik di Desa Cot Mee - Sania Alfiani (Jurnal Proyek Teknik Sipil, 2023)
The use of artesian wells or drilled wells is still the main choice of the people of Cot Mee Village, one of the areas in Nagan Raya Regency, where this is done to meet the needs of raw water sources as domestic needs. In addition to the expensive cost of installing borewells, this also adversely affects the environment due to excessive use of groundwater and raises the potensial for land subsidence. Under these circumstances, in order to solve the problem of raw water for individual lives, alternative solutions are needed that are more effective and efficient. One of alternative is to create a rainwater harvesting system from the roof of the building by maximizing high rainfall or known as rainwater harvesting technique. Field studies show the building area in Cot Mee Village is currently in good condition and livable and the entire roof is made of zinc. Of course, this condition will be very maximum in the process of harvesting rainwater. Analysis of the potensial for rain harvesting in Cot Mee Village is 64,685.61 liters/day, with the potential for rainwater harvesting per house of 743,512 liters/day. The ratio between the total water harvested amounted to 64,685.61 liters/day with the total use of raw water for needs of the people of Cot Mee Village of 43,399.8 liters/day. Research shows that rainwater harvesting technique will be adequate and able to be an alternative in providing raw water for domestic needs.